2008
DOI: 10.1111/j.1439-0264.2008.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Androgen Binding Protein, Oxytocin Receptor, Caveolin 1 and Proliferation Marker p21 in Benign Prostate Hyperplasia

Abstract: Androgen-binding protein (ABP) and oxytocin (OT) are among the factors that control smooth muscle proliferation and tumour growth through oxytocin receptor (OTR). A close functional interaction of OTR and caveolin 1 has been shown to modulate cell growth and proliferation. We investigated samples from 10 patients (mean age 68.3) who underwent transurethral prostate resection because of benign prostate hyperplasia (BPH) by immunohistochemistry. Post-mortem prostate samples of three young men (age 18, 28, 33) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
0
5
0
1
Order By: Relevance
“…The prevalence of OTRs inside caveolae has been found to be increased in BPHtissue (37). Both caveolin-1-and OTR-expression increase with age (37) and their colocalization increases in BPH patients (38).…”
Section: Oxytocin and Its Pathwaymentioning
confidence: 97%
See 2 more Smart Citations
“…The prevalence of OTRs inside caveolae has been found to be increased in BPHtissue (37). Both caveolin-1-and OTR-expression increase with age (37) and their colocalization increases in BPH patients (38).…”
Section: Oxytocin and Its Pathwaymentioning
confidence: 97%
“…The similarities of the two nonapeptides and their receptors, and their demonstrated potential to crosstalk underpins current interest in finding more selective OT-and AVP-agonists and -antagonists especially when administering the drug systemically (82). Nevertheless, the classic roles of (38) In epithelial and stromal cells: both peptides are still preserved; where OT is associated with contractile effects and social bonding whereas AVP is associated with water homeostasis and blood pressure regulation. OT acting through AVP-receptors in addition to its own receptor, might account for some of the observed OT side effects because of their possible relation to homeostasis (headache and dizziness).…”
Section: The Relevance Of Possible Crosstalk Between Oxytocin and Argmentioning
confidence: 99%
See 1 more Smart Citation
“…SHBG is an active participant in many of these age-associated physiological changes [8]. Jirikowski et al [9] have recently demonstrated that SHBG is co-localized in prostate and benign prostate hyperplasia with oxytocin. The colocalization of these two important endocrine elements in the prostate may suggest an interaction in their function in prostate cells.…”
mentioning
confidence: 98%
“…Este hormônio exerce um papel fundamental na contração do miométrio no momento do parto e na contração das células mioepiteliais da glândula mamária permitindo a ejeção do leite e lactação, apresentando receptores que circundam os alvéolos e ductos mamários (ANOUAR et al, 1996;FUCHS et al, 1996;REZAPOUR;BACKSTROM;ULMSTEN, 1996;ZINGG, 1996;IVELL, 1997;KIMURA et al, 1998;INABA et al, 1999;BAE;WATSON, 2003;THACKARE;WHITTINGTON, 2006;PRETZER, 2008;LEE et al, 2009;GORDON et al, 2010;LUI et al, 2010;DEBLON et al, 2011;MAGON;KALRA, 2011;CARSON et al, 2013 2 ; KOEHBACH et al, 2013). Outras funções da OT incluem os efeitos no sistema cardiovascular (HATAMI;VALOJERDI;MOWLA, 2007;AHMED;ELOSAILY, 2011;LOPATINA et al, 2012), a regulação da proliferação celular em diferentes tecidos (PETERSSON et al, 2002;HATAMI;VALOJERDI;MOWLA, 2007;SENDEMIR et al, 2008;ZHONG et al, 2010;VRACHNIS et al, 2011), e os efeitos no sistema nervoso central relacionados ao aprendizado, memorização, estresse, desordens neuropsiquiátricas, tendo um papel chave no comportamento social e relacionamento entre os mamíferos (OSTROWSKI, 1998;UVNAS-MOBERG et al, 2001;PRETZER, 2008;…”
Section: Introductionunclassified